Congenital Syphilis: A Discussion of Epidemiology, Diagnosis, Management, and Nurses' Role in Early Identification and Treatment. (December 2018) - Rowe, Christine R.; Newberry, Desi M.; Jnah, Amy J.
Abstract : Background: Syphilis is caused by the spirochete bacterium Treponema pallidum. Syphilis left untreated, or inadequately treated during pregnancy, can result in congenital syphilis (CS). Congenital syphilis can lead to severe sequelae or fetal, neonatal, or infant death. Purpose: To discuss the epidemiological trends, pathophysiology, diagnosis, and management of CS; the implications of CS upon the infant; as well as the importance of the nurse's role in the prompt identification of CS and the timely interventions needed to minimize sequelae. Methods: A literature search was completed using ProQuest, CINAHL, Google Scholar, and PubMed. Articles published within the past 10 years were included. Findings: Epidemiological trends of CS in the United States indicate that maternal syphilis infection and CS are on the rise. Risk factors include ethnicity, socioeconomic status, access to prenatal care, and sexual behaviors, as well as compliance with prenatal syphilis screening by prenatal providers. Risks of CS to the developing fetus begin at approximately 14 weeks. Timely treatment is necessary to minimize or eliminate mortality and morbidity. Implications for Practice: Evidence-based, interprofessional strategies, which promote a collaborative perinatal/neonatal preventative approach to care of the pregnant female, are indicated to reverse the increasing incidence of CS within the United States. Strategies prioritizing early identification and treatment of at-risk neonates are necessary to reduce/eliminate the devastating long-term consequences of CS upon this vulnerable population. Implications for Research: The paucity of research, which focuses on CS, is most likely due to ethical concerns related to infants as research participants and provides an opportunity for future research. Future research could focus on factors that focus on maternal–fetal/maternal–child transmission of CS.